Comparative study of efficacy of excimer light therapy vs intralesional triamcinolone vs topical 5% minoxidil: an observational study - Zonunsanga (Our Dermatology Online, 2015)
Introduction: Alopecia Areota is a chronic inflammatory disease that involves hair follicles, and sometimes nails, caused by T-cell mediated autoimmune mechanism. Current treatment modalities includes corticosteroids (oral, topical or intralesional), Minoxidil, Contact sensitizers like DNCB, DPCP and SADBE, Immunosuppressants like Methotrexate or Azathioprine, DMARDs like Sulfasalazine, and Phototherapy. Materials and methods: After taking consent, 40 patients treated with excimer light, 46 patients treated with triamcinolone injection intralesionally and 14 patients treated with topical minoxidil 5% were compared by their photographs taken prior to treatments, at 2 months and 6 months follow up. Results: Among the excimer group, 21/32 (61.76%) with single patch and 1/6 (16.67%) with multiple patches achieved >50% hair regrowth. Among Triamcinolone group, 23/30 (76.67%) with single patch and 10/16 (62.5%) with multiple patches achieved >50% hair regrowth. Among the Minoxidil group, 4/12 (33.33%) with single patch and none .i.e 0/2 with multiple patches achieved >50% regrowth. Conclusion: After comparing the efficacy of Excimer light therapy, intralesional triamcinolone and 5% Minoxidil, it was concluded that intralesional triamcinolone seems to be the most efficacious. Multiple patches were more resistant than single patch. Scalp response much better than beard.